IMPLEMENTASI KEBIJAKAN PENERTIBAN PASAR BARABAI DI KABUPATEN HULU SUNGAI TENGAH PROVINSI KALIMANTAN SELATAN - Ahlul Hadi Azhari (Jurnal Tatapamong, 2020)
Trade is an activity with the hope of being able to trigger the movement of the community's economy and have an impact on people's welfare. But the Barabai Modern Traditional Market has not been able to provide convenience for buyers to transact and the arrangement of traders is still chaotic because there is no orderly place to trade. Control of Barabai Modern Traditional Market aims to provide convenience in buying and selling transactions at Barabai Modern Traditional Market. The factors causing this disorder are 1) lack of public awareness 2) unclear arrangements and 3) inadequate facilities. This study uses a qualitative descriptive method with an inductive approach, for data collection methods in the form of observation, interviews and documentation. Furthermore, this study uses implementation theory from Merilee S. Grindle. The results of this study indicate that the enforcement of Barabai Modern Traditional Market has not been good with the inhibiting factor is the lack of public awareness to maintain order, the absence of decisive action and the facilities of the Barabai Modern Traditional Market. As for the socialization efforts and appeals to the community. Suggestions for the implementation of modern barabai traditional market control are in the form of making SOPs for controlling the modern barabai traditional market.